PERLINDUNGAN HAK REHABILITASI BAGI PEMAKAI, KORBAN PENYALAHGUNA DAN PECANDU NARKOBA DARI JERATAN HUKUM PIDANA - Azwar Azwar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Law enforcement against Drug Users, Victims of Drug Abuse and Drug Addicts is regulated in Law No. 35 of 2009 concerning Narcotics, which adopts two justice systems: rehabilitation justice and criminal justice. In efforts to combat drug abuse, the rehabilitation justice system is often neglected by law enforcement officials in Indonesia. Examining several articles in the Drug Law, there is synergy to create a different handling system for Drug Abusers, Victims, and Addicts. Articles 54 and 103 focus more on rehabilitation, while Article 127 provides criminal penalties but also opens up opportunities for rehabilitation for victims. According to normative legal theory, drug addicts are actually victims who suffer from illness and require physical and psychological treatment, as well as support from the community, in order to live a normal life again. Implementing prison sentences alone is not sufficient in accordance with the perspective of Law Number 35 of 2009 concerning Narcotics, which provides the right to rehabilitation for users, addicts, and victims of drug abuse, both voluntarily and through a judge's decision. However, the implementation of the right to rehabilitation for drug users in Indonesia has not reached an optimal level due to several obstacles, both internal and external. Law Number 35 of 2009, not only to provide a deterrent effect to perpetrators or prevent others from committing the same act, but also to ensure that perpetrators receive treatment, so they can return to society in a better condition. Keywords : Rights Protection, Rehabilitation, Users, Victims of Drug Abuse and Drug Addicts